Anopheles gambiae laminin interacts with the P25 surface protein of Plasmodium berghei ookinetes. - Vlachou, D; Lycett, G; Sidén-Kiamos, I; Blass, C; Sinden, R; Louis, C (2001)
Laminin is a major constituent of the basal lamina surrounding the midgut of the malaria vectors that has been implicated in the development of the Plasmodium oocyst. In this report we describe the cloning of the Anopheles gambiae gene encoding the laminin gamma 1 polypeptide and follow its expression during mosquito development. To further investigate the putative role of laminin in the transmission of the malaria parasite we studied the potential binding of the P25 surface protein of Plasmodium berghei using a yeast two-hybrid system. Heterodimer formation was observed and does not require any additional protein factors since purified fusion proteins can also bind each other in vitro. Laminin gamma 1 also interacts with the paralogue of P25, namely P28, albeit more weakly, possibly explaining why the two parasite proteins can substitute for each other in deletion mutants. This represents the first direct evidence for molecular interactions between a surface protein of the Plasmodium parasite with an Anopheles protein; the strong interplay between laminin gamma 1 and P25 suggests that this pair of proteins may function as a receptor/ligand complex regulating parasite development in the mosquito vector.